The use of adverbs in Ngor-Okpala dialect of Igbo - Nwachukwu, Emmanuel Lucas (Journal of Language, Literature, Social and Cultural Studies, 2025)
Adverbs play a crucial role in language by providing additional information about various elements of a sentence such as verbs, adjectives, other adverbs, prepositional phrases, subordinate clauses, and even complete sentences. Very little attention has been given to usage-based approach to parts of speech, particularly the use of adverbs in different dialects, this study investigates the use of adverbs in Ngor-okpala dialect of Igbo. Adverbs in Igbo language is known as Nkwuwa or Enyemaka Ngwaa, Adverbs in the dialect are used to answer questions such as "Olee ?- where, Olee nke- which, Olee otu- how,  Olee onye-who, Olee mgbe-when, Olee ihe-what, etc. It aims to understand their role, their varied usage, the implications they hold for linguistic expression and impact in the dialect. The study adopts a descriptive approach, identifying and analyzing adverbs and their usage in the Ngor-Okpala dialect, to reveal patterns of usage, syntactic structures, and semantic implications. This work adopts the Universal grammar theory. The study reveals that the use of various adverbs in the Ngor-okpala dialect help to convey details about how, when, where, how often, or to what extent an action occurs or a quality is expressed in the dialect, intensifying the meaning of the words they modify, making them a significant component of linguistic expression in Ngor-okpala dialect. The study concludes that adverb is an essential component of the dialect’s linguistic expression, providing various details about actions, qualities, and relationships within sentences. An understanding of this is crucial for effective communication in the dialect where precision and clarity are paramount.